KEMAMPUAN INFLASI PADAMODEL PURCHASING POWER PARITY DALAM MENJELASKAN NILAI TUKAR RUPIAH TERHADAP DOLLAR AMERIKA SERIKAT - Agus Budi Santosa (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2008)
This research will analyze the relationship between inflation variable with exchange valueof Rupiah toward American Dollar. The model used is Purchasing Power Parity (PPP) model byusing Error Correction Model (ECM) analysis instrument. The employment of PPP model isbased on the empirical evidence which shows the ability of PPP model in predicting andexplaining the behaviour of the exchange value. While the reason of using ECM is that it is able toexplain the long term and short term behaviour of the exchange value.The result of the result shows that in the short term period of time the inflation variabledoes not significantly influence the fluctuation of the Rupiah’s exchange value toward theAmerican Dollar and the amount of money flowing. On the other hand, national income variableand interest variable significantly influence the exchange value of Rupiah toward AmericanDollar. The main emphasis of the research is that positive direction coefficient between inflationand exchange value in the short term. The estimation result of the ECM shows that errorcorrection term (ECT) value equal zero. Therefore, it is concluded that the model used is valid.Key Words : Purchasing Power Parity, Inflasi , Error Correction Models , Kurs